Above bandgap induced photoexpansion and photobleaching in Ga-Ge-S based glasses - Messaddeq, S. H.; Li, M. S.; Lezal, D.; Ribeiro, SJL; Messaddeq, Younes [UNESP] (Elsevier B.V., 2001)
Photoexpansion and photobleaching effects have been examined in glass compositions Ga10Ge25S65 and Ga5Ge25As5S65. Such compositions are promising for optical storage and planar waveguide applications. To evaluate the photoinduced effect, samples were exposed to 351 nm light, varying power density (3-10 W/cm(2)) and exposure time (0-120 min). The exposed areas have been analyzed using atomic force microscopy (AFM) and an expansion of 800 nm is observed for composition Ga10Ge25S65 exposed during 120 min and 5 W/cm(2) power density. The optical absorption edge measured by a spectrophotometer indicates a blue shift (80 nm) after illumination in the composition Ga10Ge25S65. The morphology was examined using a scanning electron microscopy (SEM). The chemical compositions measured using a energy dispersive analyzer (EDX) indicate an increase of the number of sulfur atoms in the irradiated area. (C) 2001 Elsevier B.V. B.V. All rights reserved.